1996
DOI: 10.1177/026921639601000406
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a 'good' death: a comparative study of the views of hospice staff and patients

Abstract: The literature suggests that health professionals working in palliative care have developed an idealised concept of dying which has been labelled the 'good' death. This paper reports the results of a preliminary qualitative study which compared the concepts of a 'good' death used by patients and staff in a palliative care unit. Semistructured interviews designed to elicit perceptions of 'good' and 'bad' deaths were conducted with 18 patients and 20 health professionals. The transcribed interviews were content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(139 citation statements)
references
References 9 publications
10
122
0
7
Order By: Relevance
“…As previous studies have also found (e.g. Low and Payne, 1996;Payne et al, 1996), there was considerable consensus in how our interviewees characterized both 'good' and 'bad' deaths. A 'good' death is described primarily in terms of peacefulness, symptom control, frank conversations, acceptance and openness to physical and emotional support.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As previous studies have also found (e.g. Low and Payne, 1996;Payne et al, 1996), there was considerable consensus in how our interviewees characterized both 'good' and 'bad' deaths. A 'good' death is described primarily in terms of peacefulness, symptom control, frank conversations, acceptance and openness to physical and emotional support.…”
Section: Discussionsupporting
confidence: 55%
“…We also show that these narratives have some distinctive formal characteristics, especially in terms of the starting point and core of the action, the use of personal pronouns and metaphors, and the ways in which positive or negative evaluation is expressed. Additionally, we point out that, as noted by Payne et al (1996), the view of what constitutes a 'good' death is remarkably consistent across our interviewees. We suggest that these characteristics reflect and support a strong sense of professional worth and identity, which is undoubtedly helpful for hospice staff performing their difficult roles.…”
Section: Introductionsupporting
confidence: 70%
“…36 It thus reflects the core components of a particular professional ideology and commitment to the nature and achievement for all patients of a particular construct of 'the good death'. [37][38][39][40] This involves the excellent control of symptoms within a holistic approach to care, which acknowledges death as a natural, rather than a pathological, process. It incorporates a commitment to open awareness and communication about dying between all participants: patient, family and professionals.…”
Section: Talking About Death and Dying: Developing A Public Conversationmentioning
confidence: 99%
“…ACP has developed within a cultural and professional ideology combining commitment to the value of individual autonomy and choice and a practice of palliative care promoting a particular vision of 'the good death'. 38,39 The good death is a professionally brokered experience and focuses on the patient being comfortable, free from pain, in her or his preferred place and accompanied by family and significant others. An open awareness of dying enables communication and transparency about the circumstances of death.…”
Section: Introductionmentioning
confidence: 99%
“…34 We searched the literature and selected studies of dying patients that addressed the conceptual domains or used measures to assess quality of life or quality of dying. 5,20,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Concepts and domains from these measures were identified and listed for possible inclusion into the conceptual model and operational definition.…”
Section: Review Of Existing Instrumentsmentioning
confidence: 99%